Unraveling the effect of drought and heat stresses on grain quality of wheat (Triticum aestivum) - G A, NANDINI; CHITRANSHI, ABHISHEK; GAMPA, MALLESH; GOSWAMI, SUNEHA; DALAL, MONIKA; KUMAR, SUDHIR; TYAGI, ARUNA; KUMAR, RANJEET R (The Indian Journal of Agricultural Sciences, 2024)
Drought stress (DS) and heat stress (HS) have adverse effects on wheat (Triticum aestivum L.) growth, serving as the primary constraints that significantly limit grain yield. Present study was carried out during 2020–21 and 2021–22 at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi to evaluate the effects of drought and heat stress on grain quality parameters of 4 contrasting wheat genotypes. Several physiological and biochemical parameters were analyzed in wheat cv. C306 (thermotolerant), HD3271 (thermosusceptible), H11500 (drought tolerant) and HD3226 (drought susceptible) under DS and HS. Our study found that disintegration of chlorophyll pigments was higher in wheat cv. HD3226 (43%) under combined stress. Grain weight per spike was reduced by 30% in C306 and 47.3% in HD 3271 under combined drought and heat stress treatment. All cultivars showed reduction in starch, amylose, amylopectin, AGPase and Soluble starch synthase activity under DS and HS. Additionally, a significant increase in total soluble protein and free amino acid content were observed in all genotypes under combined stress. Chlorophyll content and grain weight per spike were positively correlated with the starch, amylose, amylopectin, soluble starch synthase and AGPase activity, while negatively related to the total soluble protein and free amino acid content. The tolerant genotypes maintained higher chlorophyll content, grain weight per spike, starch, amylose, amylopectin, soluble starch synthase and AGPase activity could be used for breeding, for the adaptation to drought and heat under climate change.